2006
DOI: 10.1051/vetres:2005054
|View full text |Cite
|
Sign up to set email alerts
|

A serological study of exposure to arthropod-borne pathogens in dogs from northeastern Spain

Abstract: -There is limited information regarding the prevalence of many vector borne pathogens in Europe and especially in Spanish dogs. We investigated 206 sick and 260 clinically healthy dogs from three different regions in northeastern Spain for antibodies to Rickettsia conorii (Rc), Ehrlichia canis (Ec), Anaplasma phagocytophilum (Ap), Bartonella henselae (Bh), Bartonella vinsonii subsp. berkhoffii (Bvb), Leishmania infantum (Li) and Borrelia burgdorferi (Bb) and for antigen of Dirofilaria immitis (Di). Total preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
99
7
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 41 publications
18
99
7
4
Order By: Relevance
“…berkhoffii. In similar studies, higher seroprevalences were reported in Sudan (65%), Morocco and Thailand (38%), similar percentages were reported in Israel (10%) and lower seroprevalences were reported in the U.S.A. (2%) and Spain (1.1%) [1,11,12,22,23]. Low level bacteremia but high seroprevalence to B. vinsonii subsp.…”
supporting
confidence: 63%
“…berkhoffii. In similar studies, higher seroprevalences were reported in Sudan (65%), Morocco and Thailand (38%), similar percentages were reported in Israel (10%) and lower seroprevalences were reported in the U.S.A. (2%) and Spain (1.1%) [1,11,12,22,23]. Low level bacteremia but high seroprevalence to B. vinsonii subsp.…”
supporting
confidence: 63%
“…Seroprevalence of Dirofilaria immitis, Ehrlichia canis and Borrelia burgdorferi in Dogs in Iğdır Province, Turkey [1] Barış SARI 1  Gencay Taşkın TAŞÇI Dirofilariosis, ehrlichiosis and lyme borreliosis are arthropod-borne diseases that are seen in domestic dogs as in many species of animals. Dogs infected with these diseases; can be diagnosed as characteristic symptoms, are shown non-spesific clinical appearance or even asymptomatic.…”
Section: Anahtar Sözcükler: Dirofilaria Immitis Ehrlichia Canis Bormentioning
confidence: 99%
“…Endpoint titers were determined as the last dilution at which brightly stained bacteria could be detected on a fluorescence microscope. Exposure to Leishmania chagasi and Rickettsia rickettsii was evaluated by IFA as described [42,45]. The cut-off dilution for seroreactivity was defined at 1:64 for R. rickettsii, and 1:80 for L. chagasi.…”
Section: Serology-based Assaysmentioning
confidence: 99%